Urinary 8-iso PGF2α and 2,3-dinor-8-iso PGF2α can be indexes of colitis-associated colorectal cancer in mice. - Yusuke Miyazaki; Tatsuro Nakamura; Shinya Takenouchi; Akane Hayashi; Keisuke Omori; Takahisa Murata (PLoS ONE)
Early diagnosis of colorectal cancer is needed to reduce the mortal consequence by cancer. Lipid mediators play critical role in progression of colitis and colitis-associated colon cancer (CAC) and some of their metabolites are excreted in urine. Here, we attempted to find novel biomarkers in urinary lipid metabolite of a murine model of CAC. Mice were received single administration of azoxymethane (AOM) and repeated administration of dextran sulfate sodium (DSS). Lipid metabolites in their urine was measured by liquid chromatography mass spectrometry and their colon was collected to perform morphological study. AOM and DSS caused inflammation and tumor formation in mouse colon. Liquid chromatography mass spectrometry-based comprehensive analysis of lipid metabolites showed that cyclooxygenase-mediated arachidonic acid (AA) metabolites, prostaglandins, and reactive oxygen species (ROS)-mediated AA metabolites, isoprostanes, were predominantly increased in the urine of tumor-bearing mice. Among that, urinary prostaglandin (PG)E2 metabolite tetranor-PGEM and PGD2 metabolite tetranor-PGDM were significantly increased in both of urine collected at the acute phase of colitis and the carcinogenesis phase. On the other hand, two F2 isoprostanes (F2-IsoPs), 8-iso PGF2α and 2,3-dinor-8-iso PGF2α, were significantly increased only in the carcinogenesis phase. Morphological study showed that infiltrated monocytes into tumor mass strongly expressed ROS generator NADPH (p22phox). These observations suggest that urinary 8-iso PGF2α and 2,3-dinor-8-iso PGF2α can be indexes of CAC.